Internationally Educated Teachers: The Sweet and Sour Journey of (Re) becoming Teachers in Canada - Yossra Othman (Canadian Journal for New Scholars in Education, 2022)
This literature review highlights the experiences of internationally-educated teachers (IETs) upon navigating the profession in some Canadian provinces. It focuses on the struggles IETs encounter that begin with disregarding most of their international qualifications, and requiring them to get requalified. This analysis of the literature synthesizes findings from 12 journal articles written by more than 30 authors, which were selected using online searches for journals focused on teacher education in Canada, and administration and policy in Canadian education. This study also examines examples of three Canadian teacher education programs, two of which are specifically designed for IETs. The study has come to find that even though some institutions are making attempts to respond to the needs of IETs, qualifying bodies use more of one-size-fits-all approach when assessing IETs credentials and experiences, and there is a need to employ a more differentiated/personalized approach in order to better assess IETs qualifications.